International Migration of Filipino Healthcare Professionals: Perspectives and Experiences of Former Employees in a Government Hospital in the Philippines - Caino, Rinalyn C.; Castillote, Grace Anne N. (Journal of Health Sciences and Medical Development, 2024)
The continuous migration of highly skilled Filipino healthcare professionals to work overseas is an occurrence that has indeed resulted in a significant loss of talent and expertise in the country’s healthcare system. The departure of these healthcare professionals often leaves their previous positions vacant, which leads to an increased workload for the remaining staff and eventually results in work overload, inefficiency, and shortage of personnel, which disrupts the seamless operation of the healthcare system, ultimately affecting the service delivery and the quality of patient care. Thus, further investigation of this perennial concern of Filipino healthcare professionals’ global mobility is imperative to understand its current context fully. Through semi-structured interviews and follow-up interviews, this qualitative study explores how a group of 14 former healthcare professionals in a government hospital in Leyte perceive international migration for work, their perceived factors for migration, and the everyday challenges they have encountered as migrant healthcare workers. The thematic analysis of interview responses revealed the following specific perspectives about former healthcare professionals’ view on international migration for work: further advance professional and career growth, establish a better work environment, aiming for competitive compensation, the problematic healthcare system in the Philippines, and safeguard employees’ mental wellbeing. Further, it was found that the healthcare professional participants considered the factors influencing their decision to work abroad: toxic work culture and work overload, non-competitive compensation and benefits, work inequality and abuse of power, and career development and progression. Three major themes emerged regarding challenges: overcoming culture shock, language barriers, communication gaps, and homesickness.